I'm proving some properties about the free groups using the categorical definition, which is the following:

Let $X$ be a set, $L$ a group and $i:X\to L$ a map. The pair $(L,i)$ is free on $X$ if for every group $H$ and every map $f:X\to H$ there exists a unique group homomorphism $\varphi:G\to H$ such that $\varphi\circ i=f$.

I've already proved that

(1) $i$ must be injective and that

(2) if $(L_1,i_2)$ and $(L_2,i_2)$ are free on $X$ then there exists $\varphi:L_1\to L_2$ such that $\varphi\circ i_1=i_2$.

Now I'm stuck with the following:

If $|X|=|Y|$ and $(L_1,i_1)$ and $(L_2,i_2)$ are free on $X$ and $Y$ respectively, then $L_1\cong L_2$.

I tried using a biyection $g:X\to Y$ and (2) to find $\varphi:L_1\to L_2$ which I can prove that is surjective. However, I cannot show that it is inyective outside $i_1(X)$, what can I do?

  • $\begingroup$ I'm going to presume something along the lines of 'Note that there must be a similar $\phi : L_2\mapsto L_1$ and prove their compositions $\phi\circ\varphi$ and $\varphi\circ\phi$ are natural isomorphisms?' $\endgroup$ – Steven Stadnicki Jul 31 '18 at 17:38

Fix a bijection $g: X\rightarrow Y$ with inverse $h: Y\rightarrow X$. Then $f_1= i_2\circ g: X\rightarrow L_2$ defines a $\varphi_1: L_1\rightarrow L_2$ and similarly $f_2= i_1\circ h: Y\rightarrow L_1$ defines a $\varphi_2: L_2\rightarrow L_1$. The composition $\varphi_2\circ \varphi_1: L_1\rightarrow L_1$ is the homomorphisms corresponding to the mapping $id_X: X\rightarrow X$. As this map "extends" uniquely to a homomorphism $L_1\rightarrow L_1$ and the identity $id_{L_1}$ is obviously such a homomorphism, we have $\varphi_2\circ \varphi_1= id_{L_1}$. Similarly $\varphi_1\circ \varphi_2= id_{L_2}$, thus $\varphi_1$ is the desired isomorphism.

  • $\begingroup$ To "extend" the map to a homomorphism $L_1\to L_1$ do I have to assume that $L_1=\langle{X}\rangle$? Something that I haven't proved yet. Otherwise I don't know how to find such homomorphism using the definition of free group. $\endgroup$ – Javi Jul 31 '18 at 18:14
  • $\begingroup$ No, it makes no difference if $X$ is contained in $L_1$ or not. I used the word extend in a loose way. $\endgroup$ – A. Pongrácz Jul 31 '18 at 18:18
  • 1
    $\begingroup$ I think you meant: "The composition $φ2∘φ1:L_1→L_1$ is the homomorphism corresponding to the mapping $i:X→L$." Since free extensions only work on maps starting at $X$ and ending at some group, which necessarily cannot be the set $X$. $\endgroup$ – Musa Al-hassy Aug 1 '18 at 15:12

While there is already an accepted answer, I'd like to showcase a more algebraic solution to the problem which is not as common.

That $L, 𝒾$ is the free group for $X$ means that there is a way to “extend” maps from $X$ to homomorphisms from $L$,

$$ ⟨\_⟩ \,:\, (X → H) \,⟶\, (L → H) $$

Such that this is indeed an extension when restricted to the elements of $X$,

$$ (0) \qquad ϕ ∘ 𝒾 = f \quad≡\quad ϕ = ⟨f⟩ $$

In (0) taking $ϕ$ to be $⟨f⟩$ yields

$$ (1) \qquad\qquad\qquad\qquad ⟨f⟩ ∘ 𝒾 = f $$

In (0) taking $ϕ, f$ to be $id, i$ yields

$$ (2) \qquad\qquad\qquad\;\;\;\;\qquad id = ⟨𝒾⟩ $$

Now suppose we are given $g : X ≅ Y$ where $X, Y$ have free groups $L₁, 𝒾₁$ and $L₂, 𝒾₂$, then we claim $⟨i₂ ∘ g⟩ : L₁ ≅ L₂$ with inverse $⟨𝒾₁ ∘ g⁻¹⟩$.

Indeed we can show this to be true with a simple calculation: --omitting the subscripts--

  ⟨𝒾 ∘ g⟩ ∘ ⟨𝒾 ∘ g⁻¹⟩ = id
≡{ Using (2) with an aim to utilising (0) }
  ⟨𝒾 ∘ g⟩ ∘ ⟨𝒾 ∘ g⁻¹⟩ = ⟨𝒾⟩
≡{ Now in a position to utilise (0) }
  ⟨𝒾 ∘ g⟩ ∘ ⟨𝒾 ∘ g⁻¹⟩ ∘ 𝒾 = 𝒾
≡⟨ The only thing we can use is (1), so let's try it }
  ⟨𝒾 ∘ g⟩ ∘ 𝒾 ∘ g⁻¹ = 𝒾
≡⟨ Again the only thing we can use is (1), so let's try it }
  𝒾 ∘ g ∘ g⁻¹ = 𝒾
≡{ Inverses and identity laws }
  𝒾 = 𝒾
≡{ Reflexivity of equality }
  • $\begingroup$ Thanks for your approach :) $\endgroup$ – Javi Aug 1 '18 at 19:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.